สมรรถนะด้านการประกอบอาชีพและการทำงานข้ามวัฒนธรรมของบัณฑิตไทยสู่ประชาคมอาเซียน - เรืองวานิช ภาสกร; ปานจันทร์ วันชัย; ชุ่มนาเสียว ปรัชญา (Ph.D. in Social Sciences Journal, 2016)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ (1) ศึกษาระดับสมรรถนะในการประกอบอาชีพและการทำงาน ข้ามวัฒนธรรมของบัณฑิตไทย (2) ศึกษาปัจจัยที่เอื้อต่อการพัฒนาสมรรถนะด้านการประกอบอาชีพและ การทำงานข้ามวัฒนธรรมของบัณฑิตไทย และ (3) เปรียบเทียบสมรรถนะด้านการประกอบอาชีพและ การทำงานข้ามวัฒนธรรมของบัณฑิตไทยสู่ประชาคมอาเซียน ผลการวิจัยพบว่า 1.) บัณฑิตที่สำเร็จการ ศึกษาในระดับอุดมศึกษาของประเทศไทย เห็นด้วยกับสมรรถนะในการประกอบอาชีพและการทำงาน ข้ามวัฒนธรรมของบัณฑิตไทยสู่ประชาคมอาเซียน โดยภาพรวมอยู่ในระดับมากทุกด้าน 2.) ผลการศึกษา ปัจจัยที่เอื้อต่อการพัฒนาสมรรถนะในการประกอบอาชีพและการทำงานข้ามวัฒนธรรมของบัณฑิตไทย บัณฑิตที่สำเร็จการศึกษาในระดับอุดมศึกษาของประเทศไทย โดยภาพรวมอยู่ในระดับมาก เรียงตาม ลำดับ ดังนี้ ด้านเศรษฐกิจ ด้านสังคมและวัฒนธรรม ด้านการศึกษา และด้านการเมือง 3.) ผลการเปรียบ เทียบสมรรถนะในการประกอบอาชีพ และการทำงานข้ามวัฒนธรรมของบัณฑิตไทยในระดับอุดมศึกษาที่ มี เพศ ต่างกัน โดยภาพรวมและรายด้านทุกด้าน ไม่แตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 4.) บัณฑิตที่สำเร็จการศึกษาในระดับอุดมศึกษาของประเทศไทยที่มีอายุ และอาชีพต่างกัน โดยภาพรวม และ แยกเป็นราย 5 ด้าน ไม่แตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 ส่วนทักษะด้านองค์ความรู้ตาม ศาสตร์สาขาวิชา มีความคิดเห็นแตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 และ 5.)บัณฑิตที่สำเร็จ การศึกษาในระดับอุดมศึกษาของประเทศไทยที่มีภูมิภาคที่อาศัยต่างกัน มีความคิดเห็นเกี่ยวกับสมรรถนะ ในการประกอบอาชีพและการทำงานข้ามวัฒนธรรมของบัณฑิตไทยสู่ประชาคมอาเซียน โดยภาพรวมและ รายด้าน 4 ด้านแตกต่างกัน ส่วนทักษะด้านภาษาและการสื่อสาร และทักษะด้านการใช้เทคโนโลยี มีความ คิดเห็นไม่แตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 COMPETENCIES IN CAREERS AND CROSS CULTURAL WORKING OF THAI GRADUATE TOWARDS ASEAN COMMUNITY This research aimed at (1) studying competencies in careers and cross cultural working of Thai Graduate, (2) studying factors that favor the development on competencies in careers and cross cultural working of Thai Graduate, and (3) comparing competencies in careers and cross cultural working of Thai Graduate towards ASEAN Community. It was found from the research that 1.) The graduate who graduated under the higher education level level of Thailand agreed on the competencies in careers and cross cultural working of Thai Graduate towards ASEAN Community in overall at very good level. When considering individually, it was found that they agreed at much level in all aspects 2.) The result from the study into the factors that favor the development on competencies in careers and cross cultural working of Thai Graduate was that Thai graduate under higher education level in overall in very good level. in order as follows: on economy, on society, and on culture, on education, and on politics. 3.) The results of the comparison of competencies in careers and cross cultural working of Thai Graduate under higher education level of Thailand had different gender, in overall and individual aspects including knowledge skill under field of study with statistical significance of .05 level. 4.)The graduate who graduated under higher education level of Thailand had different ages and different career had not different in overall and individual 5 aspects with statistical significance of .05 level. For the knowledge skill under field of study, they had different opinions at statistical significance of .05 level. and 5.) The graduate who graduated under higher education level of Thailand had different region of residence, had different in overall and individual 4 aspects with statistical significance of .05 level. For the language and communication skill and the using technology skill, they had not different opinions at statistical significance of .05 level.